Challenges and Opportunities for MSMEs in Accessing the Global Market: Qualitative Analysis through In-Depth Inter-views with Export-Oriented MSME Entrepreneurs - Endayani, Fatmasari; Sudarmiatin Sudarmiatin; Heri Pratikto (International Journal of Economics, Management and Accounting, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia's economy with a contribution of more than 60 percent to the Gross Domestic Product and the absorption of 97 percent of the national workforce, but their participation in international trade is still low with only 14 percent involved in export activities. This research aims to analyze the challenges and opportunities faced by MSMEs in accessing the global market and identify adaptation strategies developed by entrepreneurs. A qualitative method with a phenomenological approach was applied through in-depth interviews with 18 export-oriented MSME owners and managers in East Java who were selected by purposive sampling. Thematic analysis using ATLAS.ti revealed seven main challenges including limited access to capital, complexity of export regulations, constraints on production capacity and quality consistency, language and cross-cultural communication barriers, lack of international market information, logistics infrastructure problems, and intensive competition. On the other hand, four strategic opportunities were identified, namely increasing demand for sustainable authentic products, accelerating digitalization and e-commerce, utilizing free trade agreements, and ethical consumerism trends. MSMEs develop effective adaptation strategies in the form of strategic collaboration, product differentiation with premium positioning, the use of digital technology, and a focus on specific market niches. The research emphasizes that the successful internationalization of MSMEs requires a holistic approach integrating internal capacity building with the support of a conducive external ecosystem.